Morphology and pathogenicity of Fusarium isolated from pine in nurseries in Durango - Sarmiento-López, Homero; Hernández-Marín, David Alejandro; Chávez-Montes, Abelardo; García-Rodríguez, José Leonardo; Sigala-Rodríguez, José Ángel; Sánchez-García, Eduardo (Revista Mexicana de Ciencias Agrícolas, 2024)
Damping-off is a disease that occurs in forest nurseries during the establishment stage of seedlings and is mainly caused by fungi. The objective was to carry out the isolation, morphological characterization, and pathogenicity tests of fungi in five forest nurseries in the state of Durango in 2018. Fungal isolates were obtained from seedlings of Pinus engelmannii, P. durangensis, P cooperi, and P. arizonica approximately 45 days old, which were selected based on the presence of symptoms characteristic of the disease. Samples were seeded in Petri dishes containing PDA supplemented with antibiotics. Macroscopic and microscopic characteristics were recorded from colonies and structures produced in PDA, CLA and SNA media. The pathogenicity was evaluated by inoculating a suspension of conidia in the seed, and evaluating the percentage, index, and speed of germination, as well as the severity of the disease, survival analysis with Kaplan-Meier curves and the fit of epidemiological models of the progress of the disease was also determined. It was found that the fungal isolates that cause the damping-off problem in a pre-emergent and post-emergent way, obtained from seedlings of Pinus spp. in the forest nurseries of the state of Durango, were morphologically similar to isolates belonging to the F. fujikuroi and F. oxysporum species complexes. In addition, differences were observed in the severity of the disease produced by the isolates and they fitted the Gompertz model and the monomolecular model.
Keywords: F. fujikuroi; F. oxysporum; Pinus spp.; germination; survival